2010
DOI: 10.1080/14786430903482735
|View full text |Cite
|
Sign up to set email alerts
|

On the onset of void ordering in metals under neutron or heavy-ion irradiation

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…However, there are contradicting statements in the previous works about the mechanisms and dimensionality of di-interstitial SIA (di-SIA) and SIAC diffusion. 2,13,14,16,17 At the same time, the comparison with the recent experimental results showed a large discrepancy in the diffusivity of dislocation loops. 4 The understanding of the mechanisms of the production of large clusters of defects is of practical importance for reducing the irradiation embrittlement.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, there are contradicting statements in the previous works about the mechanisms and dimensionality of di-interstitial SIA (di-SIA) and SIAC diffusion. 2,13,14,16,17 At the same time, the comparison with the recent experimental results showed a large discrepancy in the diffusivity of dislocation loops. 4 The understanding of the mechanisms of the production of large clusters of defects is of practical importance for reducing the irradiation embrittlement.…”
Section: Introductionmentioning
confidence: 81%
“…Although many features of the radiation damage have been explained, several phenomena are still discussed, including the mechanisms of production of large clusters of defects and dislocation loops, 5,[8][9][10][11][12] the effect of PKA mass on the defect yield, 8,12 the influence of surfaces in the experiments with thin foils, 8 the mobility of self-interstitial atoms (SIAs), clusters (SIACs), and dislocation loops. 2,4,[13][14][15][16] One of the most plausible explanations of the formation of superlattices of bubbles [1][2][3]13,14,16 in several metals under the radiation damage is based on the anisotropic diffusion of SIAs or SIACs. However, there are contradicting statements in the previous works about the mechanisms and dimensionality of di-interstitial SIA (di-SIA) and SIAC diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. Evans * Camrose Consultants, 27 Clevelands, Abingdon, Oxon., OX14 2EQ, UK Abstract. In their recent paper on void ordering, Barashev and Golubov [1] describe cavity lattice formation in austenitic steel under electron irradiation as a bubble lattice rather than a void lattice. While this is convenient for the model they propose, this comment gives several reasons why the bubble lattice assignation cannot be justified.…”
mentioning
confidence: 99%
“…Barashev and Golubov [1] describe a model of void lattice formation based on the one dimension migration of self-interstitial atom (SIA) clusters emanating from collision cascades under neutron or heavy ion bombardment. To avoid the difficulty (to their model) of the observation of void ordering in 1 MeV electron irradiated nitrided austenitic stainless steel [4] they have repeated an interpretation of this observation by Trinkaus and Jäger [5] which suggested that the high concentration of nitrogen reported in the steel had led to the formation of a nitrogen bubble lattice, rather than a void lattice.…”
mentioning
confidence: 99%